Experimental infection of non-immunosuppressed and immunosuppressed goats reveals differential pathogenesis of Babesia aktasi n. sp. - Ozubek, Sezayi; Ulucesme, Mehmet Can; Bastos, Reginaldo G.; Alzan, Heba F.; Laughery, Jacob M.; Suarez, Carlos E.; Aktas, Munir (Frontiers in Cellular and Infection Microbiology, 2023)
Babesiosis, an acute and persistent tick-borne disease caused by protozoans called Babesia. These hemoparasites, affects vertebrates globally, resulting in symptoms such as high fever, anemia, jaundice, and even death. Advancements in molecular parasitology revealed new Babesia species/genotypes affecting sheep and goats, including Babesia aktasi n. sp. which is highly prevalent in goats from Turkiye's Mediterranean region. The objective of this study was to investigate the pathogenesis of B. aktasi n. sp. infection in immunosuppressed (n=7) and non-immunosuppressed (n=6) goats. These animals were experimentally infected with fresh B. aktasi n. sp. infected blood, and their clinical signs, hematological and serum biochemical parameters were monitored throughout the infection. In the immunosuppressed group, the presence of parasites in the blood was detected by microscopic examination between 4 and 6 days after infection, accompanied by fever and increasing parasitemia. Goats that did not survive acute disease exhibited severe clinical signs, such as anemia, hemoglobinuria, and loss of appetite. However, the goats that survived showed milder clinical signs. In the non-immunosuppressed group, piroplasm forms of B. aktasi n. sp. were observed in the blood within 2-5 days after inoculation, but with low (0.01-0.2%) parasitemia. Although these goats showed clinical findings like loss of appetite, typical signs of babesiosis were absent except for increased body temperature. Hematological analysis revealed significant decreases in the levels of red blood cells, leukocytes and platelet values post-infection in immunosuppressed goats, while no significant hematological decreases were observed in non-immunosuppressed goats. In addition, serum biochemical analysis showed elevated transaminase live enzymes levels and decreased glucose and total protein values in the immunosuppressed group post-infection. In conclusion, this study provides valuable insights into the pathogenicity of the parasite and will serve as a foundation for future research aimed at developing effective prevention and control strategies against babesiosis in small ruminants.